A comprehensive analysis of middle-European molecular sensitization profiles to pollen allergens - Panzner, Petr; Vachová, Martina; Vítovcová, Petra; Brodská, Petra; Vlas, Tomáš (International archives of allergy and immunology, 2014)
Molecular diagnosis of allergy and microarray technology have opened a completely new avenue of insight into sensitization profiles from both the clinical and the epidemiological point of view. We used this innovative tool in the description of sensitization patterns in pollen-sensitized patients in Middle Europe. Immunoglobulin E detection using 112 different allergenic molecules was carried out employing the ImmunoCAP ISAC microarray system. Sera from 826 patients sensitized to at least one pollen-derived molecule were subjected to analysis. The highest observed sensitization rate was 81.0% to grass-specific molecules (the most frequent being Phl p 1; 69.6%). The second most frequent sensitization was 54.8% to Betulaceae-specific molecules (Bet v 1; 54.2%). Together, grasses and Betulaceae components (and their cosensitizations with other components) comprised the vast majority of pollen sensitizations. Unexpectedly frequently observed sensitizations were those to Cupressaceae-specific molecules (14.1%), Oleaceae-specific molecules (10.8%), and the plane tree-derived molecule Pla a 2 (15.5%). The sensitization rates for all other molecules were within the expected range (Art v 1, 13.6%; Pla l 1, 9.6%; Che a 1, 8.4%; Par j 2, 0.9%; Amb a 1, 0.8%, and Sal k 1, 0.5%). Cross-reacting molecule sensitization rates were found to be 12.4% for profilins, 5.0% for polcalcins, and 6.4% for lipid transfer proteins. Molecular diagnosis of allergy gives a more precise and comprehensive insight into pollen sensitization patterns than extract-based testing, allowing a better understanding of the sensitization process and regional differences. The data presented here may help to improve the diagnostic and allergen-specific treatment procedures in the respective region.
Keywords: zkřížené reakce; Retrospective Studies; Evropa; imunoanalýza; sezónní alergická rýma; alergeny; Allergens; Pollen; pyl; mikročipová analýza; retrospektivní studie; Humans; Microarray Analysis; Rhinitis, Allergic, Seasonal; Cross Reactions; Immunoassay; lidé; Europe